Do ocular pulse amplitude and choroidal thickness change in patients with thyroid eye disease?. (3rd September 2019) - Ozturk Karabulut, Gamze; Fazil, Korhan; Ozturker, Can; Gunaydin, Zehra Karaağaç; Altan, Cigdem; İnal, Asli; Taskapili, Muhittin; Kaynak, Pelin
ABSTRACT: Purpose : The aim of this study was to evaluate whether orbital changes induced by thyroid eye disease affect the ocular pulse amplitude and choroidal perfusion. Materials and Methods : A total of 38 eyes of 38 patients with thyroid eye disease (Group 1) and 38 eyes of 38 control individuals (Group 2) with normal intraocular pressure were enrolled in this study. Thyroid eye disease activity was defined using clinical activity score. Intraocular pressure measurement with Goldmann applanation tonometer, axial length, central corneal thickness, Hertel exophthalmometry and systolic and diastolic blood pressure measurements were taken from each patient. Ocular pulse amplitude and intraocular pressure were measured using dynamic contour tonometry. Choroidal thickness was measured by enhanced depth imaging-optical coherence tomography at subfoveal, nasal and temporal 1000 μm area. Results : Intraocular pressures measured with Goldmann applanation tonometer and dynamic contour tonometry and mean ocular pulse amplitude were not statistically different between groups. However mean choroidal thicknesses were significantly lower when compared to control group. Ocular pulse amplitude and intraocular pressure measurement with dynamic contour tonometry did not change significantly with the increase in clinical activity score. There was not statistically significant correlation between ocular pulse amplitude and choroidal thicknesses in patients with thyroid eye disease. Conclusion : Ocular pulse amplitude and choroidal perfusion were not found to change with orbital involvement in thyroid eye disease and with disease activity, especially in patients with normal intraocular pressure. Although choroidal thickness was thinner than control group, choroidal perfusion did not change as a compensatory mechanism for maintaining ocular homeostasis.